Morphological assessment of the regeneratory function of the tooth root cement with destructive periodontitis - V. V. Glinkin; M. A. Gasbanov; Z. K. Makhmudova; Z. M. Gasanova; O. Leizerovitz (Эндодонтия Today, 2022)
Aim: to provide a morphological study of the areas of cement resorption of the tooth root to assess the regenerative function of cement in destructive forms of periodontitis.Materials and methods. The studies were carried out on scanning electron and light microscopes.Results. It was found that in some places resorption lacunae and cement defects of the root of the tooth are filled with granulation tissue and cement cells. The cementum and periodontal tissues are closely related. Cement cells are covered with components of the extracellular matrix (ECM), which is synthesized by connective tissue cells.Conclusions. Given the presence of poorly differentiated cells in the periodontal tissues, it is possible to restore the tissue of the cementum of the tooth root if adequate conditions are created during the treatment process.